Sirt1 Promotes the Restoration of Hepatic Progenitor Cell (HPC)-Mediated Liver Fatty Injury in NAFLD Through Activating the Wnt/β-Catenin Signal Pathway - Li, Qinjin; Gong, Yuqing; Wang, Yi; Liu, Bingbing; Chu, Yi; Gui, Sisi; Zheng, Yazhen; Chen, Xiaodong (Frontiers in Nutrition, 2021)
Non-alcoholic fatty liver disease (NAFLD) has developed into the world's largest chronic epidemic. In NAFLD, hepatic steatosis causes hepatocytes dysfunction and even apoptosis. Liver has a strong restoration or regeneration ability after injury, however, it is unclear through which pattern fatty liver injury in NAFLD is repaired and what the repair mechanism is. Here, we found that in HFD-induced NAFLD mice model, fatty liver injury caused significant ductular reaction (DR), which is a marker to promote the repair of liver injury. SOX9+and HNF4α+ biphenotype also suggested that hepatic progenitor cells (HPCs) were activated by fatty liver injury in HFD-elicited NAFLD mice model. Concurrently, fatty liver injury also activated Wnt/β-catenin signal pathway, which is a necessary process for HPCs differentiation into mature hepatocytes. However, Sirt1 knockdown weakened HPCs activation and Wnt/β-catenin signal in Sirt1+/-mice with HFD feeding. In rat-derived WB-F344 hepatic stem cell line, Sirt1 overexpression (OE) or Sirt1 activator‒Resveratrol promoted HPCs differentiation via activating Wnt/β-catenin signal pathway. Glycogen PAS staining demonstrated that Sirt1 OE promoted WB-F344 cells to differentiate into mature hepatocytes with glycogen synthesis ability, while Sirt1 inhibitor EX527 or Wnt/β-catenin pathway inhibitor HF535 decreased obviously glycogen positive cells. Together, our data suggested that Sirt1 plays a vital role in activating HPCs to repair fatty liver injury or promote liver regeneration through Wnt/β-catenin signal pathway in NAFLD, which might provide a new strategy for fatty liver injury or NAFLD therapy.